2021
DOI: 10.1002/aisy.202000090
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopy Reveals Abnormal Changes in the Urine Composition of Prostate Cancer: An Application of an Intelligent Diagnostic Model with a Deep Learning Algorithm

Abstract: Early diagnosis of prostate cancer (PCa) is always a great challenge in clinical practice, especially in distinguishing benign prostatic hyperplasia (BPH) from early cancer, due to the high similarity in pathology from the prostate‐specific antigen (PSA) test and radiological detection. The conventional diagnostic methods are often less efficient in specificity and accuracy, leading to quite a few unnecessary biopsies. This work establishes a noninvasive diagnostic method for PCa by investigating urine samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…[47] Chen et al integrated Raman spectroscopy with CNNs to introduce a novel approach for detecting PCa through urine analysis. [48] PCa and prostatic hyperplasia (BPH) are discernible through variations in the intensity of the characteristic peaks related to lipids, NAs, and selected amino acids within the urine Raman spectra. This differential pattern indicates the presence of anomalous metabolic activity associated with PCa, which can be captured by Raman spectroscopy.…”
Section: Multivariate Analysis Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…[47] Chen et al integrated Raman spectroscopy with CNNs to introduce a novel approach for detecting PCa through urine analysis. [48] PCa and prostatic hyperplasia (BPH) are discernible through variations in the intensity of the characteristic peaks related to lipids, NAs, and selected amino acids within the urine Raman spectra. This differential pattern indicates the presence of anomalous metabolic activity associated with PCa, which can be captured by Raman spectroscopy.…”
Section: Multivariate Analysis Toolsmentioning
confidence: 99%
“…In Figure 6b, (i) presents the bright-field image and the area indicated by the arrow is rich in lipids and drug compounds; (ii) displays the reconstructed Raman image of the sample [48] Copyright 2021, Wiley-VCH. This study directly integrates a data-processing engine into the acquisition flow to address the current drawbacks of conventional Raman systems.…”
Section: Combination With Fiber and Nanoparticles (Nps)mentioning
confidence: 99%
“…Owing to these discoveries so far, there is no doubt that detecting more accurately spectral peak differences, implementing more accurate algorithms and building more accurate diagnostic models have become a new challenge. With the help of Raman spectroscopy and convolutional neural network (CNN) algorithm to study urine samples, Chen et al (2021) established a non-invasive diagnostic method for prostate carcinoma. Obviously, the results of urine Raman spectroscopy showed that the intensity of characteristic peaks of lipids, nucleic acids and some amino acids of prostate carcinoma and BPH could be distinguished, and then these data were used to train an intelligent diagnostic model of CNN algorithm to deep study, and the idea of using urine Raman spectroscopy combined with deep learning technology to diagnose prostate carcinoma provides a reference for the application of artificial intelligence in the field of clinical medical research.…”
Section: Application In Prostate Diseasesmentioning
confidence: 99%
“…[5][6][7] Especially, the high false positives (≈75%) in the PSA gray zone of 4-10 ng mL −1 lead to many unnecessary biopsies, [8,9] which aggravate the medical/physiological burden of patients and affect their life quality. [8,10] Meanwhile, imaging techniques such as ultrasound and magnetic resonance (MR) suffer from low accuracy, high costs, radiologist dependency, and time-consuming testing, rendering them unsuitable for the practical, precise screening of PCa in the gray zone. [11,12] In this context, a precise and noninvasive platform is desirable for PCa diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] As the most widely used biomarker for PCa screening, the prostate-specific antigen (PSA) provides limited sensitivity and specificity, which may lead to overdiagnosis and subsequent overtreatment. [5][6][7] Especially, the high false positives (≈75%) in the PSA gray zone of 4-10 ng mL −1 lead to many unnecessary biopsies, [8,9] which aggravate the medical/physiological burden of patients and affect their life quality. [8,10] Meanwhile, imaging techniques such as ultrasound and magnetic resonance (MR) suffer from low accuracy, high costs, radiologist dependency, and time-consuming testing, rendering them unsuitable for the practical, precise screening of PCa in the gray zone.…”
Section: Introductionmentioning
confidence: 99%